A cost minimization study on the allocation of teaching overload using linear programming the UPV-CAS perspective. - Padojinog, Winston Conrad B (1989.)
Subject overload honoraria constitutes one of the items of expenditures competing for the scarce financial resource of the UPV College of Arts and Sciences. Since the financial resource is limited, efficient resource utilization is imperative. Thus, the cost in this area of concern must be minimized., To realize cost minimization for subject overload honoraria, the study sought the optimal combination in allocating subjects between the lecturers and faculty using quantitative tool-linear programming. It then compared the proposed scheme of subject overload against the current practice. Linear programming, specifically of the simplex method, was used to derive the optimal utilization and allocation of the subject overload. In the process of deriving the cost coefficients for the different variables, it was found that it is less costly to extend overload honoraria to faculty members than hire lecturer. Data output show that subject overloads will be more economical when give to those faculty members on the Instructor I level and gradually up towards the higher faculty ranks. Furthermore, the scheme of subject overloading proposed by the study is comparatively lower than what the current practice adopts. This confirms that the mathematical tool of linear programming is a workable instrument to utilize in analyzing cost. Thus, making it a sound basis for rational decision making. This study therefore proposes that the applicability of linear programming to other divisions and GE subjects be further studied. Moreover, it is recommended that a study be undertaken to apply linear programming to other areas of expenditures, such as those items of capital outlay (equipment, facilities), maintenance and other operating costs in the entire UPV financial structure.
Thesis (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Teaching